Students Learning Outcomes and Internalization Islamic Values in Buffer Solution Concept through Online Learning - Leny Heliawati; Anna Permanasari; Uun Sundari (Jurnal Tadris Kimiya, 2021)
This study analyses students learning outcomes and internalization of Islamic values in buffer solutions through online learning during the Covid-19 pandemic. The study was conducted to find effective strategies in achieving students’ competence and Islamic values. This research is a quasi-experimental study conducted on 100 tenth-grade students using The One Group Pretest-Posttest model. The results showed students learning outcomes obtain an N-Gain value of 0.72 (high category). The internalization of Islamic values for three aspects: praying, blessing, and study hard determined the average above 3 (often do). Thus, the research concludes that online learning conducted on buffer materials is effective in mastering the content and internalization of Islamic values.